2012
DOI: 10.5137/1019-5149.jtn.6669-12.1
|View full text |Cite
|
Sign up to set email alerts
|

Missed injury in patients with severe traumatic brain injury complicated by multiple trauma

Abstract: AIm:The aim of this study was to investigate retrospectively the multiple injuries prone to be missed in 432 cases. mAterIAl and methOds:The cases were divided into two groups, i.e., whether the missed injury was found during admission or follow up. The mean ISS value, ratio of patients of cases with GCS < 8, and mortality were calculated and compared. The incidences of missed diagnosis of various body parts were calculated and compared with one another to identify the multiple injuries prone to be missed duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…Optic nerve injury is an easily ignored case, especially in brain hernia patients. A 2013 study on 432 polytraumatized patients reported that 3 patients suffered from TON, which diagnosis have been missed in 2 of them leading to patient disability in one case [22]. Indirect injury to the optic nerve following head trauma occurs as a result of shearing of the nerve fibers, interruption of blood supply, or secondary edema and hemorrhage following shearing or transection of the optic nerve vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Optic nerve injury is an easily ignored case, especially in brain hernia patients. A 2013 study on 432 polytraumatized patients reported that 3 patients suffered from TON, which diagnosis have been missed in 2 of them leading to patient disability in one case [22]. Indirect injury to the optic nerve following head trauma occurs as a result of shearing of the nerve fibers, interruption of blood supply, or secondary edema and hemorrhage following shearing or transection of the optic nerve vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have demonstrated that a higher ISS has a significant relationship with missed injuries in trauma patients [16][17][18][19][20]. The ISS is an established medical score used to assess trauma severity and is correlated with mortality, morbidity, and hospitalization duration after trauma.…”
Section: Discussionmentioning
confidence: 99%
“…The storage and processing of such a substantial number of keys bring many overheads, especially in terms of memory. To overcome such issues, compression techniques can be integrated with the PPCT to reduce the storage consumption in the platform [21,22]. Apart from employing compression techniques, parallel architectures can be employed rather than serial architectures to match the keys of infected individuals to find the potentially exposed contacts [23].…”
Section: Lack Of Compression Techniques To Seamlessly Reduce Computin...mentioning
confidence: 99%